3D Imaging Resolves Human Pancreatic Duct-β-Cell Clusters During Cystic Change - Lee, Chih-Yuan; Kuo, Ting-Chun; Chou, Ya-Hsien; Peng, Shih-Jung; Hsiao, Fu-Ting; Chung, Mei-Hsin; Lo, Li-Wen; Shen, Chia-Ning; Chien, Hung-Jen; Chang, Hsiu-Pi; Chen, Chien-Chia; Jeng, Yung-Ming; et al. (Diabetes (New York, N.Y.), 2025)
Pancreatic cystic changes in adults are increasingly identified through advanced cross-sectional imaging. However, the impact of initial/intra-lobular epithelial remodeling on the local β-cell population remains unclear. In this study, we examined 10 human cadaveric donor pancreases (tail and body regions) via integration of stereomicroscopy, clinical H&E histology, and 3D immunohistochemistry, identifying 36 microcysts (size: 1.22±0.56 mm) alongside 54 low-grade pancreatic intraepithelial neoplasias (positive control of epithelial remodeling; size: 2.42±1.05 mm). Both conditions exhibited significant increases in CK7 and insulin immunoreactive signals compared with normal lobules. Importantly, despite luminal contents of microcysts causing false positives (autofluorescence) in fluorescence imaging, the defined cystic epithelium showed distinct duct-β-cell associations—including β-cells in the epithelium and duct-β-cell clusters—visualized via antifade 3D/Airyscan super-resolution imaging in the high-refractive-index polymer. The peri-luminal β-cells displayed insulin+ vesicles residing near the basal domain, while the CK7+ cytokeratins in duct cells accumulated in the apical domain, underlining polarized tissue and cellular organizations. Overall, in microcyst formation, we demonstrate local and associated pancreatic exocrine and endocrine tissue remodeling. Because artifacts are a concern in β-cell investigation in a novel environment, our work using 3D-labeled human pancreas with cytokeratin and vesicle resolving powers provides a robust approach for characterizing the duct-β-cell association in a clinically relevant setting.